Jenis Kelelawar Pemakan Buah (Pteropodidae) di Taman Wisata Alam Gunung Meja Manokwari - Freddy Pattiselanno; Petrus I. Bumbut (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
A study of bats was aimed to collect information on the presence of fruit bats that predicted involved in pollination or seed dispersal of certain commercial fruit plants within and around the Taman Wisata Alam Gunung Meja, Manokwari. Forty five individual consists of 8 (eight) species: Dobsonia minor, Dobsonia moluccensis, Macroglossus minimus, Nyctimene aello, Nyctimene albiventer, Nyctimene draconilla, Rousettus amlexicaudatus and Syconicteris australis have been captured and identified during the survey. It was assumed based on observation of vegetation found around the study site that the presence of fruit bats species help to maintain and contribute to seed dispersal of the fruit plants. Further study is required to obtain accurate data through the stomach content collection of the observed bats. Land conversion and illegal hunting was frightened influence the bat habitat and population which finally impact to fruit production.